A unique small molecule class of fluorophores with large Stokes shift based on the electron deficient 9-methoxypyrroloisoquinolinetrione core. (July 2022) - Khitrov, Michael D.; Platonov, Dmitry N.; Belyy, Alexander Yu; Trainov, Konstantin P.; Velmiskina, Julia A.; Medvedev, Michael G.; Salikov, Rinat F.; Tomilov, Yury V.
Abstract: A novel fluorescent core based on electron-deficient 9-methoxypyrroloisoquinolinetrione moiety with a condensed imide cycle is developed. The new class of dyes show large Stokes shift up to 6519 cm-1 (Δλ up to 130 nm), however, unlike parent 5-hydroxyisoquinolones, 9-methoxypyrroloisoquinolinetrione are not superphotoacidic which could be responsible for the large Stokes shifts. At the same time methylation of 5-hydroxyisoquinolones reduces Stokes shift from 5086 to 4689 cm-1. The increase in Stokes shift upon the formation of an imide cycle was shown to be due to unusual bond-lengths relaxation involving the imide ring. Graphical abstract: Image 1 Highlights: Fluorescent electron-deficient 9-methoxypyrroloisoquinolinetriones are developed. The new class of dyes show large Stokes shift up to 6519 cm-1 (Δλ up to 130 nm). The large Stokes shift is due to unusual bond-lengths relaxation.